The evolution of global midwifery education from ancient practices to modern standards. - Asnawi, Damia Hazimah; Hashim, Sarena H; Abdul-Mumin, Khadizah H (British Journal of Midwifery, 2026)
Midwifery began as community-based care and has since evolved into a structured and regulated profession. This article traces the evolution of midwifery education, illustrating how it has developed across global and local contexts. In many high-income countries, midwifery education has become standardised, ensuring midwives receive formal training and accreditation. However, disparities persist in low- and middle-income countries, where access to education, resources and professional recognition varies widely. Global organisations and national regulatory bodies have played a key role in shaping modern midwifery education, ensuring competency standards and professional accountability. Despite these advancements, midwives worldwide face workforce shortages, inconsistent regulations and barriers to full professional autonomy. Midwifery education must continue evolving by embracing new technologies, modernising curricula and advocating for stronger policies. By working towards global alignment in midwifery training and drawing lessons from Brunei Darussalam, all women can receive high-quality maternal and newborn care.